Appropriate dosing of sugammadex to reverse deep rocuronium‐induced neuromuscular blockade in morbidly obese patients. (19th December 2015) - Loupec, T.; Frasca, D.; Rousseau, N.; Faure, J.‐P.; Mimoz, O.; Debaene, B.
Summary: In morbidly obese patients, the speed of reversal of neuromuscular blockade with sugammadex based on ideal body weight is still matter of debate. In this single‐center, randomised, double‐blinded study, neuromuscular blockade was monitored in 50 patients using acceleromyography at the adductor pollicis. At the end of surgery with deep rocuronium‐induced neuromuscular blockade, patients randomly received sugammadex 4 mg.kg −1 (high dose group), 2 mg.kg −1 (middle dose group), or 1 mg.kg −1 (low dose group) of ideal body weight. After administration of the first dose of sugammadex, the mean (SD) recovery time (censored at 600 s) from deep neuromuscular blockade was significantly shorter (p < 0.001) in the high‐dose group (n = 14; 255 (63) s) vs the middle‐dose group (n = 13; 429 (102) s), or low‐dose group (n = 4; 581 (154) s). Success rate from neuromuscular blockade reversal defined by a train‐of‐four ≥ 0.9 within 10 min after sugammadex administration, were 93%, 77% and 22% for these high, middle and low‐dose groups respectively (p < 0.05 vs low‐dose group). In morbidly obese patients, 4 mg.kg −1 of ideal body weight of sugammadex allows suitable reversal of deep rocuronium‐induced neuromuscular blockade. Monitoring remains essential to detect residual curarisation or recurarisation.